THE INFLUENCE OF HABITUS AND GADGET MEDIA DEPENDENCE ON SLEEP PATTERNS OF ADOLESCENT IN KETAJEN VILLAGE - Innabella Qurrotul Azizah; Isa Anshori; Ikke Wahyu Pramesty (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This study aims to explore the influence of excessive gadget use on adolescent sleep patterns in Ketajen Village. A quantitative approach was used with a survey method through a questionnaire to 50 adolescents aged 15-19 years. The questionnaire consisted of 15 questions covering the duration of gadget use, frequency of use before bedtime, and the impact on sleep quality. Data were analyzed using descriptive statistics to identify respondents' characteristics, as well as Pearson correlation and linear regression to evaluate the relationship and influence of gadget use on sleep patterns. The results showed that 75% of the respondents used gadgets for more than 3 hours a day, with 62.5% experiencing difficulty falling asleep and sleep duration of less than 7 hours each night. A total of 87.5% felt tired when they woke up, and another 87.5% woke up in the middle of the night to check their gadgets. Gadget use before bed also impacted concentration and daily activities. This study contributes to the international literature by focusing on the relationship between technology use and sleep quality in a rural context. Practically, the findings can be used by parents, educators and policy makers to manage gadget use to improve adolescents' sleep quality.